Analisis SWOT dan Framework Implementasi Strategi Pengembangan UMKM - Fadlurrahman, Fadlurrahman; Orbawati, Eny Boedi; Pajrin, Rani; Mukti, Ari; Raharjo, Budi (Universitas Indo Global Mandiri, 2023)
Magelang City UMKM actors operate in three fields, namely industry, services and trade. The development of UMKM actors in Magelang City from 2020 to 2022 experienced fluctuations. UMKM players are encouraged to expand their marketing through market places. The emergence of various digital platforms indicates that UMKM players are in the era of globalization. The development of UMKM which is accompanied by environmental changes must be adjusted to approproate strateges such as SWOT analysis approach. The aim of this research is create a model or framework for implementing UMKM development strategies in Magelang City. The research method is qualitative with a SWOT analysis approach (identification of strengths, weaknesses, opportunities and threats). The location of the research was in Magelang City. Informants were selected using a purposive sampling technique, including heads of UMKM associations, trader coordinators and regional apparatus organizations related to UMKM empowerment. Data collection was carried out by interviews, observation and documentation. This research identified 6 strengths, 7 weaknesses, 7 opportunities and 4 threats. From this identification, 16 strategies were produced in the form of 7 SO strategies, 3 WO strategies, 3 ST strategies, and 3 WT strategies. After that, a strategy implementation framework was formulated which focused on the classification of action planning for UMKM actors by paying attention to SO, WO, ST and WT strategies. All of these strategies are classified into four components, including optimizing the availability of human resources, utilizing external programs and technology, obtaining and using business legality, and forming branding and business characteristics.